A fully disposable and integrated paper-based device for nucleic acid extraction, amplification and detection. Issue 7 (8th March 2017) - Tang, Ruihua; Yang, Hui; Gong, Yan; You, MinLi; Liu, Zhi; Choi, Jane Ru; Wen, Ting; Qu, Zhiguo; Mei, Qibing; Xu, Feng
Abstract : A fully disposable and integrated paper-based device by integrating nucleic acid extraction, amplification and LFA could achieve nucleic acid testing. Abstract : Nucleic acid testing (NAT) has been widely used for disease diagnosis, food safety control and environmental monitoring. At present, NAT mainly involves nucleic acid extraction, amplification and detection steps that heavily rely on large equipment and skilled workers, making the test expensive, time-consuming, and thus less suitable for point-of-care (POC) applications. With advances in paper-based microfluidic technologies, various integrated paper-based devices have recently been developed for NAT, which however require off-chip reagent storage, complex operation steps and equipment-dependent nucleic acid amplification, restricting their use for POC testing. To overcome these challenges, we demonstrate a fully disposable and integrated paper-based sample-in-answer-out device for NAT by integrating nucleic acid extraction, helicase-dependent isothermal amplification and lateral flow assay detection into one paper device. This simple device allows on-chip dried reagent storage and equipment-free nucleic acid amplification with simple operation steps, which could be performed by untrained users in remote settings. The proposed device consists of a sponge-based reservoir and a paper-based valve for nucleic acid extraction, an integrated battery, a PTC ultrathin heater, temperature control switch and on-chip dried enzyme mix storage for isothermal amplification, and a lateral flow test strip for naked-eye detection. It can sensitively detect Salmonella typhimurium, as a model target, with a detection limit of as low as 10 2 CFU ml −1 in wastewater and egg, and 10 3 CFU ml −1 in milk and juice in about an hour. This fully disposable and integrated paper-based device has great potential for future POC applications in resource-limited settings.